2018
DOI: 10.3390/s18103454
|View full text |Cite
|
Sign up to set email alerts
|

An Operational Tool for the Automatic Detection and Removal of Border Noise in Sentinel-1 GRD Products

Abstract: The presence of border noise in Sentinel-1 Ground Range Detected (GRD) products is an undesired processing artifact that limits their full exploitation in a number of applications. All of the Sentinel-1 GRD products generated before March 2018—more than 800,000—are affected by this particular type of noise. In March 2018, an official fix was deployed that solved the problem for a large portion of the newly generated products, but it did not cover the entire range of products, hence the need for an operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The results indicated that the CR could effectively separate the three crops in the late period of crop growth. Mattia et al and Satalino et al also showed that phenology and vegetation structure changes most likely dominate the change in CR during stem extension and heading [21,64,65]. In addition, both the decrease and the strong increase related to phenology (flowering and ripening) also contribute to this change, as also observed by Wiseman et al [66] and Veloso et al [21].…”
Section: Discussionmentioning
confidence: 73%
“…The results indicated that the CR could effectively separate the three crops in the late period of crop growth. Mattia et al and Satalino et al also showed that phenology and vegetation structure changes most likely dominate the change in CR during stem extension and heading [21,64,65]. In addition, both the decrease and the strong increase related to phenology (flowering and ripening) also contribute to this change, as also observed by Wiseman et al [66] and Veloso et al [21].…”
Section: Discussionmentioning
confidence: 73%
“…GEE provides Sentinel-1 VV polarization Ground Range Detected (GRD) images which are already preprocessed using Sentinel-1 algorithm [ 48 ]. The preprocessing includes (i) Orbital file correction to eliminate the orbital noise; (ii) Thermal noise correction to eliminate the noise in the data produced by the sensors during data acquisition process onboard the satellite [ 49 ]. Thermal noise can affect the quality of the data in the areas having low mean signal response detected by the SAR system like lakes, standing water, rivers, etc., (iii) Radiometric calibration, to calibrate RADAR reflectivity (DN) to backscattering coefficient (physical units) which is mainly performed to compare the SAR images of different acquisition dates; and (iv) Terrain correction, to convert Sentinel-1 SLC (Single look complex) data from slant range geometry to a map coordinate system, and to rectify the distortions like foreshortening, layover, or shadowing effects.…”
Section: Methodsmentioning
confidence: 99%
“…Calibration: Calibration is the procedure that converts digital pixel values to radiometrically calibrated SAR backscatter [13].…”
Section: Methodsmentioning
confidence: 99%